Planeacion de los experimentos - Escobar Giron, J.A. (United Nations Development Programme, 1985)
A detailed discussion is presented on the general concepts concerning the planning of expt., with emphasis on the exptl. approach, the basic elements of the expt., and information analysis. (CIAT)